RADIATION PROTECTION OF BELARUS POPULATION OF AFTER THE CHERNOBYL DISASTER - Ja. E. Kenigsberg; N. N. Tsybulko (Радиационная гигиена)
The  article  describes  the  evolution  of  the  formation  of  the  conceptual  approaches  and  regulation documents for the population radiation protection the after the Chernobyl disaster in Belarus. Zoning scheme showing Belarus contamination is given as well as the dynamics of the quantity of settlements located in the contaminated areas, and population living in them. The methodology of regulation of radionuclides content in the foodstuffs is stated. The data on the population effective exposure doses changing is given for the post-accident period.